Peran Edukasi Keamanan Pangan dalam Meningkatkan Praktik Higiene Pengelola Kantin Universitas Mataram - Moegiratul Amaro; Mutia Devi Ariyana; Firman Fajar Perdhana; Rossy Fortuna; Baiq Rien Handayani; Wiharyani Werdiningsih; Tri Isti Rahayu; Elya Antariksana Bachmida; Dona Ulpa; Yesica Marcelina Romauli Sinaga; Sri Widyastuti (Rengganis Jurnal Pengabdian Masyarakat, 2026)
Food safety is a vital aspect of food service, especially in higher education facilities, which tend to have high food consumption rates and involve diverse consumer groups. Low awareness and suboptimal implementation of food safety practices by canteen managers or food handlers can increase the risk of foodborne illnesses that have an impact on the health of the academic community. Therefore, this community service activity was carried out with the aim of increasing the knowledge, awareness, and skills of Mataram University canteen managers in implementing food safety principles appropriately and sustainably. The methods used in this activity included interactive workshops on the basic concepts of food safety, introduction to the types and sources of potential food hazards (biological, chemical, and physical) in the food processing process, and the application of the five keys to food safety. The effectiveness of the program was evaluated through pre-tests and post-tests to measure the increase in participants' knowledge, as well as observations of participants' participation and enthusiasm during the activity. The evaluation results showed an increase in participants' level of understanding from the moderate category of 56% to the high category of 81%. These findings indicate that the community service activity had a positive impact in increasing the capacity of canteen managers, supporting the establishment of a healthier and more safe canteen environment, and contributing to the prevention of foodborne diseases on campus.